Material Pelindung Radiasi Ramah Lingkungan: Tinjauan Komprehensif Material Alternatif Pengganti Timbal untuk Aplikasi Proteksi Radiasi - Nurhasmi, Nurhasmi (Pinisi: Physics Journal, 2025)
The use of lead-based radiation shielding materials continues to face increasing rejection due to their toxicity, substantial weight, and incompatibility with sustainability principles. Recent research has driven the development of safer and lighter alternative materials that provide radiation attenuation effectiveness comparable to, or even surpassing, that of lead. This review article summarizes advancements in geopolymers, environmentally friendly heavy concrete, and polymer composites enriched with heavy metals as lead-free radiation shielding materials. Lattice vibration interactions, particularly optical phonons, are also discussed due to their growing relevance in enhancing photon-energy absorption in polymer composites. This review is intended to provide a comprehensive overview of emerging trends, underlying mechanisms, and the implementation potential of next-generation alternative radiation shielding materials